SPEAKING STRATEGIES USED BY EFL STUDENTS IN ACADEMIC SPEAKING CLASS OF ENGLISH EDUCATION STUDY PROGRAM AT UNIVERSITAS MARITIM RAJA ALI HAJI - English Education FKIP (Juliet, 2020)
Speaking considered to be a not easy skill to deal with. As everything need strategies in achieving something, also does speaking. It needs an appropriate strategy in learning process. The objective of this research is to determine speaking strategies used by EFL students at fourth semester of English education study program who are taking academic speaking class at Universitas Maritim Raja Ali Haji Tanjungpinang. This research is descriptive qualitative research. The SILL questionnaire designed by Rebecca Oxford (1990) version 7.0 was adopted as the instrument to collect the data for this research. The data were processed and analyzed through SPSS 16. Of the sixty-five fourth semester students, only fifty-four of them who submitted the answer sheet on time. The result of this research revealed that the fourth semester students of english education study program are usually used social and metacognitive strategies in their speaking learning as it proved by the high average score. For the social strategies, the average is 3.59 and metacognitive strategies is 3.52. Based on the SILL Profile of Result, those scores were categorized as high level means they usually used it in their speaking learning. Another four strategies were categorized as medium level means they sometimes used the strategies in their speaking learning, are cognitive strategies (3.43), compensation strategies (3.42), memory strategies (3.26) and affective strategies (3.19).